Perbaikan Jaringan Tegangan Rendah Dengan Sisip Trafo Distribusi Fase Tunggal Untuk Mengurangi Overload dan Jatuh Tegangan PT PLN (Persero) ULP Yogyakarta Kota - Ramadhan, Muhammad Dwi Cahyo; Ginting, Nina Loenca Br; Muflih, Haidar Nabil; Ningrum, Nur Risya Difa Kusuma; Nugraha, Candra Febri (Majalah Ilmiah Teknologi Elektro, 2024)
Distribution transformers play a crucial role in the distribution network by transforming electrical energy from the source to the customers. This is closely related to issues in the process of distributing electrical energy. According to PLN standards, a transformer is considered overloaded when the load exceeds 80% of its installed capacity. Overloading can lead to increased transformer temperature, potentially damaging the insulation and causing power supply disruptions to consumers. A B&D 50kVA distribution transformer has been installed on pole 17A/U3-30 in the Belibis Street, Wonocatur, Banguntapan, Yogyakarta area. The transformer is currently experiencing a load of 112.5%. In this study, the insertion of an additional transformer is proposed as a solution to reduce the overload percentage and voltage drop. The transformer insertion has already been implemented in the field, and this study aims to analyze its impact by determining the optimal location through simulations. Based on the simulation results using ETAP 12.6.0, the transformer insertion on pole 1/S3-19 in the field can improve the voltage value at the customer end to 0.94 p.u., with a load of 86.6% on the inserted transformer and 35.6% on the existing transformer. However, an optimal location determination is found on pole 18/S3-17 based on the best voltage value at the customer end, which is 0.94 p.u., with the existing transformer operating at 58.1% load and the inserted transformer operating at 65.3% load. The inserted transformer can effectively reduce overload and voltage drop for customers, and by determining the optimal location, it can enhance the efficiency of analyzing load development and voltage values. Keywords— transformer; overload; drop voltage; ETAP; optimal